2018
DOI: 10.3389/fphys.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity in Cardiac Innervation and Its Potential Role in Atrial Fibrillation

Abstract: Synaptic plasticity is defined as the ability of synapses to change their strength of transmission. Plasticity of synaptic connections in the brain is a major focus of neuroscience research, as it is the primary mechanism underpinning learning and memory. Beyond the brain however, plasticity in peripheral neurons is less well understood, particularly in the neurons innervating the heart. The atria receive rich innervation from the autonomic branch of the peripheral nervous system. Sympathetic neurons are clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 133 publications
0
16
0
Order By: Relevance
“…Mechanical disruption or pharmacological blockade of parasympathetic innervation has been reported to shorten ventricular refractory periods and increase the incidence of ventricular arrhythmia in murine hearts (Herring et al, 2019;Jungen et al, 2017). Many studies, using diverse recording techniques, species, and levels of cellular organization have considered the properties of mammalian intrinsic cardiac ganglion neurons (Ashton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical disruption or pharmacological blockade of parasympathetic innervation has been reported to shorten ventricular refractory periods and increase the incidence of ventricular arrhythmia in murine hearts (Herring et al, 2019;Jungen et al, 2017). Many studies, using diverse recording techniques, species, and levels of cellular organization have considered the properties of mammalian intrinsic cardiac ganglion neurons (Ashton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions are in accord with previous clinical study studies indicating that LF and the LF/HF ratio were both upregulated in OSA patients [ 28 ]. Previous clinical and basic studies had confirmed that sympathetic hyperactivity was closely related to AF inducibility [ 30 32 ]. Similarly, in our study, we found that HRV variation was consistent with atrial electrophysiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stimulation of GP in the left atrial fat pad lowers the threshold for atrial fibrillation, whilst their ablation can prevent it [ 199 , 200 ]. However, because of the intricated GP network, their role in physiological regulation of the CCS, innervation, and modulation of ventricles, ablation procedures can have serious side-effects, among them ventricular fibrillation [ 209 ]. Furthermore, neuronal remodeling (e.g., an increased presence of sympathetic neurons) has been reported in atrial fibrillation, which could have an effect on the outcome of ablation therapy [ 7 ].…”
Section: Cardiac Innervation and Heart Diseasementioning
confidence: 99%